Perceptions and Paradoxes: Exploring Graduate Students’ Attitudes towards Generative AI’s Role in Higher Education - Tangente, Sanny Jr.; Bahian, Patricia D. (Journal of Education and Learning Reviews, 2025)
Background and Aim: This study investigates the attitudes of graduate students toward generative artificial intelligence (AI) technologies in the context of higher education. Specifically, it examines students’ level of knowledge, willingness to use, and concerns regarding the educational application of generative AI tools such as ChatGPT. Materials and Methods: Anchored on a descriptive-correlational research design, the study employed quantitative methods to gather data from the 134 graduate students using a validated survey instrument. Results: Findings revealed that participants generally exhibited a moderate level of understanding, a high degree of willingness to use generative AI, and moderate levels of concern related to its potential impact on academic integrity, skill development, and social interaction. Statistically significant differences were found between knowledge, willingness, and concern levels. However, correlation analyses showed no significant relationships between the frequency of AI usage and the three attitude dimensions, indicating that regular exposure does not necessarily lead to increased understanding or reduced concern. Furthermore, the findings highlight the importance of cultivating reflective engagement and critical awareness among graduate students as they navigate the opportunities and limitations of emerging technologies in their academic pursuits. Conclusion: This study contributes to the growing body of literature on AI in education and offers actionable insights for institutional policy, curriculum development, and further research. This study extends the current understanding by revealing specific attitudes within the context of graduate education in the Philippines, a perspective largely absent in the existing literature.